2019
DOI: 10.1111/coa.13289
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic performance of ultrasonography and computerized tomography in differentiating superficial from deep lobe parotid tumours

Abstract: Objectives To validate and compare ultrasound (US) versus computerized tomography (CT) criteria in the localisation of superficial/deep lobe tumours of the parotid gland. Design and setting This was a retrospective study of diagnostic tests performed from January 2008 to June 2017. Participants We included adult patients who were referred for a neck ultrasonography examination due to parotid tumours, and who subsequently underwent parotid surgery. Main outcome measures We assessed the location of parotid tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Cheng et al (2019) showed that the US assessment of the minimum distance between the parotid fascia and the parotid tumor (MFTD) with a cutoff value of 2.4 mm can be used to differentiate the location of benign tumors in the parotid gland; distance of less than 2.4 mm correlates with the tumor localization in the superficial lobe of the parotid gland [22]. On the other hand, for a more precise and objective localization of tumors in the parotid glands with the help of the US, a schematic diagram based on marking the tumor location in relation to the external ear structures was proposed.…”
Section: Grayscale and Doppler Criteriamentioning
confidence: 99%
“…Cheng et al (2019) showed that the US assessment of the minimum distance between the parotid fascia and the parotid tumor (MFTD) with a cutoff value of 2.4 mm can be used to differentiate the location of benign tumors in the parotid gland; distance of less than 2.4 mm correlates with the tumor localization in the superficial lobe of the parotid gland [22]. On the other hand, for a more precise and objective localization of tumors in the parotid glands with the help of the US, a schematic diagram based on marking the tumor location in relation to the external ear structures was proposed.…”
Section: Grayscale and Doppler Criteriamentioning
confidence: 99%
“…The diagnostic accuracy of our procedure is superior compared to the existing studies . Lesion contact with the FN and localizing the lesion in the correct lobe were correctly predicted in 96% of the patients.…”
Section: Discussionmentioning
confidence: 76%
“…The diagnostic accuracy of our procedure is superior compared to the existing studies. [11][12][13][14]24 Lesion contact with the FN and localizing the lesion in the correct lobe were correctly predicted in 96% of the patients. As the FN is the boundary between the superficial lobe and the DL of the parotid gland, accurately localizing the nerve is crucial for predicting the correct lobe.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…US, which has the advantage of being safe, widely available, easily performed, and low cost, is usually the first tool used to evaluate major salivary gland tumors in Taiwan. 14,15 Furthermore, in-office US operated by the surgeon, who is familiar with the patient's history and physical exam findings, has become more and more common. After the real-time imaging and evaluating the characteristics of the tumor, the surgeon can make an immediate assessment for the patient.…”
Section: Discussionmentioning
confidence: 99%